How political skill and work engagement differ by hierarchical level: evidence from Brazil - Matos de Moraes, Romulo; Santos Crespo Istoe, Rosalee; Afonso Miranda, Valtair (Review of Business Management, 2023)
Objective – To analyze how the levels of Political Skill in the Organization and Engagement at Work vary between managers at different hierarchical levels in the studied scenario. Theoretical Framework – The research is based on the literature on leadership in line with recent studies on politics and engagement in work environments. Methodology – The differences in the study variables, their effects and relationships were verified by Multivariate Analysis of Variance in a sample (n=308) with professionals from three segments of the Brazilian private sector. The political skill measurement instrument was adapted and validated for Portuguese. Results – The hierarchical level affected the linear interaction between Engagement and Political Skill, however, in the scenario studied, politics played a greater role in this dynamic. The results suggest that being engaged at work is a constant attribute for managers regardless of managerial position, while political skill in the organization was gradually greater with each evolution in the hierarchical level. Practical implications – Leadership development programs are expected to consider the weight of political skill in their actions and planning, especially for activities in which the need to negotiate, influence and develop networking is crucial. The study indicates that the combination of engagement and political skill presents an opportunity to be explored in the search for hierarchical advancement. Contributions – The findings expand current knowledge about the relationships between the study constructs by presenting evidence of their intrinsic interactions with the hierarchical position of managers. Keywords: hierarchical level, political skill, engagement, managers.